2016
DOI: 10.1111/evo.13098
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of reduced individual heterogeneity in adult survival of long-lived species

Abstract: The canalization hypothesis postulates that the rate at which trait variation generates variation in the average individual fitness in a population determines how buffered traits are against environmental and genetic factors. The ranking of a species on the slow-fast continuum - the covariation among life-history traits describing species-specific life cycles along a gradient going from a long life, slow maturity, and low annual reproductive output, to a short life, fast maturity, and high annual reproductive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 36 publications
(67 reference statements)
1
38
0
Order By: Relevance
“…This prediction, is supported for survival by results from a comparative study on 11 populations belonging to 9 species situated on the slow‐fast continuum (Péron et al. ) but needs to be further investigated in future studies.…”
Section: Discussionmentioning
confidence: 68%
“…This prediction, is supported for survival by results from a comparative study on 11 populations belonging to 9 species situated on the slow‐fast continuum (Péron et al. ) but needs to be further investigated in future studies.…”
Section: Discussionmentioning
confidence: 68%
“…This is because if good environmental conditions during the first part of life (i.e., during development and early‐reproductive life) result in higher reproductive investment in early adult life, investment in late‐life reproduction should be reduced, potentially increasing the rates of reproductive senescence. In addition, if a correlation between developmental and late‐life environment was what was driving the effect of developmental environment on senescence, we would expect to see a significant effect in survival senescence rates (Reichert et al ; Bleu et al ; Le Coeur et al ; Péron et al ), in addition to the observed effect on reproductive senescence rates.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, hunter‐harvested ducks are hypothesized to have lower natural survival probabilities than those not harvested (Sedinger and Herzog , Péron ). Compared to other waterfowl, ducks are short‐lived species and are therefore expected to display greater levels of heterogeneity in survival probabilities relative to longer‐lived species that implement bet‐hedging strategies to minimize annual mortality risks and buffer against genetic and environmental perturbations through a process known as canalization (Waddington , Nevoux et al , Péron et al ).…”
mentioning
confidence: 99%
“…Tests of the condition bias hypothesis have been limited among longer‐lived waterfowl, such as geese. Inferences from the canalization hypothesis predict reduced individual heterogeneity in annual survival and body condition because of their longer life spans (Péron et al ). Morez et al () did not find support for a harvest condition bias in either juvenile or adult decoy‐harvested greater snow geese ( Anser caerulescens atlanticus ) relative to individuals captured in baited or un‐baited rocket nets.…”
mentioning
confidence: 99%